The Relationship Between Diabetes Mellitus Patients' Knowledge About The Four Pillars Of Diabetes Mellitus With Self Care At RSU Imelda Medan - Silaban, Nataria Yanti; Ritonga, E Sanda Arief; Naibaho, Eka Nugraha V; Siburian, Christine Handayani (SEAN Institute, 2023)
Diabetes militus (DM) is a non-communicable disease with a set of symptoms that arise in individuals as a result of the individual's glucose levels are above normal. Until now diabetes mellitus has not been cured, requires high treatment costs when it gets worse, and can cause various forms of complications and even death. To improve the quality of life of diabetes mellitus patients, it is necessary to increase self-care. Self care is an action taken by individuals to manage DM, in the form of treatment and prevention of complications The purpose of the study was to determine the relationship between knowledge of diabetes mellitus patients about the four pillars of diabetes mellitus with self care at RSU Imelda Medan. This research is a quantitative research using a correlational analytical design using a cross sectional approach. This research place was at RSU Imelda Medan in August 2022 with a sample of 37 respondents. The results of the study had a positive and significant relationship between Diabetes Mellitus Patients' Knowledge About the Four Pillars of DM with Self Care in Diabetes Mellitus patients at RSU Imelda Medan with the results p = 0.000, so it can be concluded that Ha accepted that there is a meaningful relationship between there is a meaningful relationship between Diabetes Mellitus Patients' Knowledge About the Four Pillars of DM with Self Care in Diabetes Mellitus patients.